-15+9=k

Simple and best practice solution for -15+9=k equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -15+9=k equation:


Simplifying
-15 + 9 = k

Combine like terms: -15 + 9 = -6
-6 = k

Solving
-6 = k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-1k' to each side of the equation.
-6 + -1k = k + -1k

Combine like terms: k + -1k = 0
-6 + -1k = 0

Add '6' to each side of the equation.
-6 + 6 + -1k = 0 + 6

Combine like terms: -6 + 6 = 0
0 + -1k = 0 + 6
-1k = 0 + 6

Combine like terms: 0 + 6 = 6
-1k = 6

Divide each side by '-1'.
k = -6

Simplifying
k = -6

See similar equations:

| 2x^2a+2xa^2=0 | | 2x+3(-1+x)=5(-1+x)+8 | | -9t=2+56 | | 9.2=-52x+4(10x+3.3) | | n/2+3 | | 3(x+4)=3(8+2x) | | x+57=19 | | a=-4+(-5) | | x-4/2=-12 | | 81x^2-45x-36= | | 2x+3y=5y+8 | | 26-38x=2(-9x-3) | | -23z+234=97 | | f=5/9(c-32) | | x+47+x+121=166 | | 1/6d+2=5/6d | | n/2+6 | | X-1/3y=1 | | -90-10x-50=500 | | 2b^2-7b-49= | | 6ax^2+9ax+15a=0 | | 3x+1+90+2x+4=180 | | .16666666667d+2=.83333333333d | | 4*107*57*107+136*107=x | | 18a^2+30a-12= | | 1/3x+1/5x+1120=x | | -18+4x=8x-6 | | c/2.5=-4.2 | | 7/2x=15/x+6 | | 4ax^2+10ax+6a=0 | | (15+y)x=10 | | 12x^4a+8x^2a^2=0 |

Equations solver categories